An effective technique in nerve defect repair: Analysis of sliding epineural tube graft technique and comparison with autologous nerve graft and turn-over epineural tube graft techniques - Kara, Murat; Koçer, Uğur; Arslan, Ramazan; Gürsoy, Koray; Vural, Seçil; Fırat, Ayşegül (Acta Medica, 2023)
Objective: Autologous nerve graft (ANG) is the standard of care in the reconstruction of nerve gaps. However, scarification of a donor nerve, donor-site complications (wound complications, sensory dysfunction, neuroma, etc.) and unpredictable results lead surgeons to search for alternative techniques. Epineural tube graft (ETG) is a good option in the repair of nerve gaps. At this point, the present study aims to analyze the utility of the sliding epineural tube graft (SETG)technique in the reconstruction of nerve gaps. Materials and Methods: Thirty Wistar albino rats were divided into five groups according to the repair technique of a 7 mm nerve defect created on the right sciatic nerve. In Group 1 the defect was left unrepaired as a negative control group. The defect was repaired with ANG in Group 2, with turn-over ETG (TETG) in Group 3, with one-directional SETG (O-SETG) in Group 4 and with bi-directional SETG (B-SETG) in Group 5. On the 12th week of the experiment, electrophysiologic, gross macroscopic and microscopic evaluation of muscle function and microscopic assessments of muscle and nerve samples were performed. The left limb and proximal nerve segment of the defect area were used as the control side. Results: Electrophysiologic, macroscopic (wet muscle weight) and microscopic (axonal count, muscle fiber thickness was superior in the ANG group compared with TETG and SETG techniques. B-SETG showed poor results in all of the aforementioned findings. TETG and O-SETG techniques showed similar neuromuscular functions. Conclusion: Although the ANG technique has some disadvantages depending on the sacrification of a donor nerve and donor side, it has significantly superior reconstructive outcomes compared to ETG techniques. However, since the ETG techniques provide acceptable results, they should be in surgeons’ treatment repertoire because of the unique features of the microsurgical intervention.